Are Horses Like Zebras, or Vice Versa? Children's Sensitivity to the Asymmetries of Directional Comparisons. Issue 2 (5th January 2016) - Chestnut, Eleanor K.; Markman, Ellen M.
Abstract : Adults exhibit strong preferences when framing symmetrical relations. Adults prefer, for example, "A zebra is like a horse" to "A horse is like a zebra, " and "The bicycle is near the building" to "The building is near the bicycle." This is because directional syntax requires more typical or prominent items (i.e., reference points) to be placed in the complement position. Three experiments with children ages 4–8 ( N  = 181) explored whether children share this sensitivity to directional syntax. Children of this age showed an incipient preference for framing reference points as complements. Stating, "Girls do math as well as boys, " which frames boys as the reference point for girls, may therefore actually teach children that boys set the standard.